2022
DOI: 10.3390/agronomy12030587
|View full text |Cite
|
Sign up to set email alerts
|

Meloidogyne graminicola’s Effect on Growth Performance of Rice under Low Population Density

Abstract: Meloidogyne graminicola is a destructive soil-borne pathogen that causes rice yield losses (Oryza sativa L.) in tropical and subtropical areas. This study investigated the effect of M. graminicola population densities on plant height, heading, and the photosynthetic parameters of rice in a greenhouse. Two-week-old rice plants were inoculated with different M. graminicola densities (250, 500, 750, 1000, 1500, and 2000 J2s/plant) and observations were recorded at 30, 60, and 90 days after inoculation (DAI). Redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In a previous study, the nematode infections in tomato plants reduced or altered photosynthetic pigments in tomato plants [ 58 ]. Chen et al [ 59 ] also determined that the leaf chlorophyll content of rice plants decreased after infection with M. graminicola , with an inoculum density ranging from 500 to 2000 J2s per plant. Further demonstrated that the tomato plant inoculation with the highest inoculum (2000 J2s/plant) resulted in a considerable reduction in chlorophyll a (80.19%), chlorophyll b (55.12%), carotenoids (67.21%), and total chlorophyll content (74.32%) as compared to the control or non-inoculated plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, the nematode infections in tomato plants reduced or altered photosynthetic pigments in tomato plants [ 58 ]. Chen et al [ 59 ] also determined that the leaf chlorophyll content of rice plants decreased after infection with M. graminicola , with an inoculum density ranging from 500 to 2000 J2s per plant. Further demonstrated that the tomato plant inoculation with the highest inoculum (2000 J2s/plant) resulted in a considerable reduction in chlorophyll a (80.19%), chlorophyll b (55.12%), carotenoids (67.21%), and total chlorophyll content (74.32%) as compared to the control or non-inoculated plants.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the current investigation demonstrate that the inoculation of nematodes resulted in a noteworthy decrease in various leaf gas exchange characteristics. The previous research investigation was conducted with rice plant inoculation with RKN juveniles (100, 500, 1000, and 2000 J2s/plant), which resulted in a significant decrease in the photosynthetic process [ 59 ]. Therefore, the density of the nematode population was adversely associated with the photosynthesis rate.…”
Section: Discussionmentioning
confidence: 99%
“…These changes harm plant health, resulting in inadequate development ( Gullino et al, 2019 ). In addition, RKNs alter physiological and metabolic functions, such as photosynthesis in plants, along with their physical attributes ( Chen et al, 2022 ). RKNs have complex interactions with their hosts and the plant genes that are induced during a compatible plant–nematode interaction.…”
mentioning
confidence: 99%